The rise of the modern monetary system: An integration of the credit and state money approaches - L. Randall Wray (Levy Economics Institute of Bard College, 2025)
This working paper integrates the credit money approach (associated with Post Keynesian endogenous money theory) with the state money approach (associated with Modern Money Theory) by drawing on Wray's 1990 book (Money and Credit in Capitalist Economies: The Endogenous Money Approach, Edward Elgar), his 1998 book (Understanding Modern Money: the Key to Full Employment and Price Stability, Edward Elgar), and his 2004 edited book (Credit and State Theories of Money: The Contributions of A. Mitchell Innes, Edward Elgar). New sources and interpretation of the history of money make it clear that there is no contradiction between state money and private credit money-each played a role in the creation of the modern monetary system. Indeed, today's system was created by bringing state money into the private money giro, thereby strengthening both.
Keywords: B25; B52; E42; E58; E62; N11; N20; 330; credit money; state money; Modern Money Theory (MMT); Bank of England; fiat money; giro money; history of money; central bank; nominalism; origins of money